Use of the tabaraq method in early childhood education - Zainal Bakri; Dinn Wahyudin (Balai Diklat Keagamaan Ambon, 2022)
Early Childhood Education is a crucial thing that must be considered by teachers and parents. This period is the golden age for children who can determine their future. The success of early childhood education can be a good starting point for children in determining their interests and future direction. However, sometimes people think Early Childhood Education is just a game, without prioritizing learning for children. One of the interesting breakthroughs in the tabaraq method in early childhood. This method is a way of memorizing Al-Qur’an that can be applied to early childhood. One of the schools that uses the tabaraq method is the AZ Tabaraq Early Childhood Education School which is the location of the research. This research is qualitative research with a descriptive research type. The aim is to find out the use of the tabaraq method in learning. By conducting observations and interviews, it was found that AZ Tabaraq carried out a class 1 tabaraq program specifically for toddlers, with an age range of 3-5 years. The purpose of this program is for children to memorize Al-Qur'an juz 30 and daily prayers. From the implementation, methods, and evaluations used, it can be concluded that the use of the tabaraq method is quite significant in helping children memorize the Al-Quran.